The Mediating Role of Intrinsic Motivation in the Relationship Between Organizational Support and Quantitative Workload and Work-Related Fatigue - Kumalasari, Lisa Dewi; Elgeka, Honey Wahyuni Sugiharto (Jurnal Sains Psikologi, 2024)
Increasingly tight job competition means that workers often ignore work-related fatigue conditions, which can negatively impact workers and organizations, resulting in decreased health and work effectiveness and even work accidents. In order to prevent this, proper work-related fatigue management is needed. This research examines the role of intrinsic motivation as a mediator in the relationship between organizational support and quantitative workload with work-related fatigue. This research is quantitative research with a survey method. The sampling technique used was stratified random sampling. The measuring instruments used are the Occupational Fatigue Exhaustion/Recovery Scale (OFER), the Quantitative Workload Inventory (QWI), the short version of the Survey of Perceived Organizational Support (SPOS), and the Situational Motivation Scale (SIMS). Data analysis used path analysis and bootstrapping in SmartPLS 3.0. The analysis results show no mediating role for intrinsic motivation in the relationship between organizational support and quantitative workload with work-related fatigue. A high quantitative workload triggers increased work-related fatigue, so it needs to be balanced with sufficient organizational support.